Schistosoma Mansoni schistosomula Antigens Induce Th1/ Pro-inflammatory Cytokine Responses - Egesa, Moses; Lubyayi, Lawrence; Tukahebwa, Edridah M.; Bagaya, Bernard S.; Wilson, Shona; Yazdanbakhsh, Maria; Labuda, Lucja A.; Cose, Stephen (Parasite immunology, 2018)
Larvae of Schistosoma (schistosomula) are highly susceptible to host immune responses and are attractive prophylactic vaccine targets, although cellular immune responses against schistosomula antigens in endemic human populations are not well characterized. We collected blood and stool from 54 Schistosoma mansoni-infected Ugandans, isolated peripheral blood mononuclear cells and stimulated them for 24 hours with schistosome adult worm and soluble egg antigens (AWA and SEA), along with schistosomula recombinant proteins rSmKK7, Lymphocyte Antigen 6 isoforms (rSmLy6A and rSmLy6B), tetraspanin isoforms (rSmTSP6 and rSmTSP7). Cytokines, chemokines and growth factors were measured in the culture supernatants using a multiplex luminex assay, and infection intensity was determined before and at 1 year after praziquantel (PZQ) treatment using the Kato-Katz method. Cellular responses were grouped and the relationship between groups of correlated cellular responses and infection intensity before and after PZQ treatment was investigated. AWA and SEA induced mainly Th2 responses. In contrast, rSmLy6B, rSmTSP6 and rSmTSP7 induced Th1/pro-inflammatory responses. While recombinant antigens rSmKK7 and rSmLy6A did not induce a Th1/pro-inflammatory response, they had an association with pre-treatment infection intensity after adjusting for age and sex. Testing more schistosomula antigens using this approach could provide immune-epidemiology identifiers necessary for prioritizing next generation schistosomiasis vaccine candidates.
Keywords: Cytokine; Antigens; Schistosomula